The West Africa Agricultural Productivity Program - Stads, Gert-Jan; Beintema, Nienke M. (International Food Policy Research Institute, 2017)
WAAPP supports the generation, dissemination, and adoption of improved technologies; the creation of enabling conditions for regional cooperation; and the development of human and institutional capacity across the subregion; along with the creation of youth employment, the participation of women, and adaption to climate change.